Impacts of Nitrogen Sources and Rates on Soil Chemical Attributes and Potato Nutrition and Yield in a Subtropical Environment - Yagi, Renato; Bagio, Bárbara; Soratto, Rogério P.; Chiachia, Thaís R. S.; Almeida, Danilo S. (Potato research, 2025)
The nutritional status, the soil chemical attributes prior to vine killing, and the classified yield of tubers may characterise soil–plant interactions with nitrogen (N) sidedressing for potato cultivars. Two experiments with potato cultivars Agata and Atlantic were carried out with the aim of evaluating the effects of N sources (urea, ammonium sulfate, and calcium nitrate) and N application rates (70, 140, and 210 kg ha −1 ) as sidedressing, plus a zero-N control treatment, in southern Brazil. Discrete variations in nutrients in diagnostic leaves and in soil chemical attributes in the Agata experiment were not reflected in the maximum average increase of 69.0% (14.2 Mg ha −1 ) in total tuber yield obtained with the calculated rate for maximum technical efficiency of 152 kg N ha −1 as ammonium sulfate or calcium nitrate. These N sources did not differ in agronomic efficiency (AE). For the Atlantic cultivar, urea was practically inert in terms of soil and plant attributes, and the ammonium sulfate addition acidified the soil, increased its Al 3+ concentration in the ridges, reduced the foliar Ca and Mg concentrations, and did not increase the marketable tuber yield. Calcium nitrate increased foliar N, Ca, and Mg concentrations, increasing marketable tuber yields by 26.6% (7.3 Mg ha −1 ) with 116.7% higher AE than other N sources. In subtropical acidic inceptisols with potentially available Al 3+ , 153 kg N ha −1 ammonium sulfate or calcium nitrate for the cultivar Agata and 152 kg N ha −1 as calcium nitrate for the cultivar Atlantic are the best options for sidedressing fertilisation.